Developing a Basic Medical Insurance Statement in Chinese Underdeveloped Areas - Hongpu HU; Yanli XU; Qingkun CHEN; Juan LI; Chenliu YANG; Yanli WAN (Tehran University of Medical Sciences, 2018)
Background: We presented the running state of rural basic medical insurance system in Henan and discussed the enforcements and development experiences of underdeveloped areas. We provided data evidence to support the improvement and development of a basic rural medical insurance system. Methods: We selected Henan Province, China as a sample, using the method of cluster sampling, from policy documents published in the national and provincial level of the new rural cooperative medical policy and work documents, data from 2004 to 2014, the National Health Statistical Yearbook of health statistics yearbook of Henan Province and relevant statistical data of the province. Results: The new rural cooperative policy has covered the whole population in Henan Province. The number of individual received benefits is increasing. In 2013, the number of persons counted has reached to 270 million, funds raised and expenditures reached 38.5 billion and 26 billion, respectively. The operational task force has been developed rapidly. In 2013, on average each staff managed the cases for 16.4 thousand rural residents. Conclusion: The major implementation and development experience from the new rural cooperative policy of Henan province include: education of related knowledge, optimization of compensation plan, development of operational system and framework, improvement of management rules, reinforcement of information system development and financial supervision and increment of investment in rural medical healthcare.